2019
DOI: 10.1155/2019/8153250
|View full text |Cite
|
Sign up to set email alerts
|

Biodentine™ Partial Pulpotomy of a Young Permanent Molar with Signs and Symptoms Indicative of Irreversible Pulpitis and Periapical Lesion: A Case Report of a Five-Year Follow-Up

Abstract: The purpose of this paper was to report the five-year success of Biodentine™ partial pulpotomy in a young permanent molar, with signs and symptoms indicative of irreversible pulpitis and periapical lesion, in a nine-year-old girl. Preoperative clinical examination revealed a large carious lesion of the left mandibular permanent first molar. The patient reported pain on percussion. The tooth responded positively to the electric pulp test and had lingering pain after cold testing. A periapical radiograph showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…There are also some studies showing that pulp preservation of young permanent teeth may have broader indications. For the indication of pulpotomy, the size of the pulp exposure, the time, and the location of pulp exposure, whether it is irreversible pulp inflammation and even periapical periodontitis, are not necessarily related [39][40][41][42][43][44][45][46]. It is suggested that the status and repairing ability of the pulp have more important significance in the prognosis of pulpotomy [47].…”
Section: Pulpotomy Of Young Permanentmentioning
confidence: 99%
“…There are also some studies showing that pulp preservation of young permanent teeth may have broader indications. For the indication of pulpotomy, the size of the pulp exposure, the time, and the location of pulp exposure, whether it is irreversible pulp inflammation and even periapical periodontitis, are not necessarily related [39][40][41][42][43][44][45][46]. It is suggested that the status and repairing ability of the pulp have more important significance in the prognosis of pulpotomy [47].…”
Section: Pulpotomy Of Young Permanentmentioning
confidence: 99%
“…Biodentine (Septodont, Saint-Maur des-Fossés, France), one of the new-generation, bioactive endodontic cements, has been claimed to have improved properties over MTA. 23 It is a is a calcium silicate-based material that has fetched attention in recent years and became commercially available in 2009.It was initially & specifically designed as a "dentin replacement material'. Biodentine is primarily formulated using the MTA -based cement technology with improvement in some properties of these types of cements such as physical qualities and handling.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium hydroxide has a long history of use as a pulpcapping agent for IPT and it may still have some advantages. However, after the advent of MTA in its various forms [iRoot BP, Biodentine, Portland cement (PC), and calcium-enriched mixture], it has become the most widely used pulp capping biomaterial (18,19,24,34,35). Most of these MTA pulp capping materials displayed similar clinical success rates when used in a partial pulpotomy, but iRoot BP was more convenient to handle because it was premixed (36).…”
Section: Partial Pulpotomy Of the Exposed Dental Pulpmentioning
confidence: 99%
“…However, most dentists inevitably modified their treatment procedures based on their clinical judgment. It was demonstrated that IPT with partial pulp necrosis and symptomatic apical periodontitis could achieve successful outcomes by the partial pulpotomy (18,19), which could be explained that the pulp of immature permanent teeth had a strong disease resistance and repair function due to its unique physiological and anatomical characteristics (7). In addition, it was also explained that the clinical diagnosis of pulp status was inaccurate, especially for traumatic teeth (67).…”
Section: Clinical Issues and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation